Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XXVII 2023
DOI: 10.1117/12.2652616
|View full text |Cite
|
Sign up to set email alerts
|

Large area robotically assisted optical coherence tomography (LARA-OCT) for skin imaging with MHz-OCT surface tracking

Abstract: Optical coherence tomography (OCT) is a powerful imaging technique to non-invasively differentiate between healthy skin and pathological conditions. Unfortunately, commercially available OCT-systems are typically slow and not capable of scanning large areas at reasonable speed. Since skin lesions may extend over several square centimeters, potential inflammatory infiltrates remain undetected. Here, we present large area robotically assisted OCT (LARA-OCT) for skin imaging. Therefor a collaborative robot is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Although the R-OCT system is mainly demonstrated for kidney imaging, we envision such a platform is generalizable to other anatomies such as skin 39 and brain 48 , as well as other applications such as cancer imaging (ATCM has been used in differentiating tumor from normal tissues 49 ). Alternative tissue analysis can be conducted using, for instance, deep-learning based reasoning for tumor diagnosis procedure 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the R-OCT system is mainly demonstrated for kidney imaging, we envision such a platform is generalizable to other anatomies such as skin 39 and brain 48 , as well as other applications such as cancer imaging (ATCM has been used in differentiating tumor from normal tissues 49 ). Alternative tissue analysis can be conducted using, for instance, deep-learning based reasoning for tumor diagnosis procedure 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al presented an R-OCT 37 that scans large tissue and generates wide FOV 3D OCT volume via stitching spatially connected small FOV volumes which were acquired by a 3D OCT probe at multiple predefined locations. Similar volume stitching principle was then applied in other R-OCT systems by He et al for in vivo whole mouse brain OCT angiography 38 and Göb et al for large area skin imaging 39 .…”
Section: Introductionmentioning
confidence: 97%
“…With future software implementations it will be possible to simultaneously acquire and store volumes while previewing live OCT data and extracting surface information. To find the correct timing of scan parameters and the velocity of robot motion, several parameter combinations were tested and a cartesian velocity of 70 mm/s was determined as optimum [ 29 ]. The sweep bandwidth of the laser was reduced to 22 nm to gain axial imaging range to account for the uneven surface of the hand and fingers.…”
Section: Large Area Imagingmentioning
confidence: 99%
“…In previous studies, multiple techniques have been utilized to expand the lateral field of view (FOV) of OCT. These approaches are distinct from expanding the lateral FOV of a single OCT scan through the use of wide-angle camera lenses [ 25 ] or the acquisition of multiple single FOVs using translational motion stages [ 26 28 ] or robotic arms [ 24 , 29 37 ] for creating a mosaic of individual scans in post. Song et al demonstrated an OCT system that could scan an approximately 200 × 200 mm 2 area in one scan by using a wide-angle camera lens and a 100 kHz swept source laser with a 500 × 500 A-Scans resolution within ∼2.5 s [ 25 ].…”
Section: Introductionmentioning
confidence: 99%